Actividad física en Medellín: desafío para la promoción de la salud (2008)
ABSTRACT: Chronic diseases generate high economical and social costs to humankind. The lack of physical activity has been considered as a determinant factor in the epidemics of chronic diseases nowadays. It is mandatory to explore this kind of behavior in order to outline appropriate actions for prevention and health promotion. Method: a survey on 3.979 representative people of both sexes from Medellín, Colombia was carried out evaluating attitudes and practices related to physical activity and its associated factors. The analysis included the description of proportions with their respective tests of statistical significance and different crossings with sociodemographic variables. Results: only one out of five people (21.2%) performs enough physical activity in order to protect its health. Physical activity is higher among men and is positively associated to social-economic levels and education status. The sedentary behavior is usually adopted in early stages of youth and is kept throughout lifespan. Physical activity, on the contrary, is usually associated to a better balance in body composition. Conclusion: the high prevalence of sedentary behaviors in the population is probably becoming a significant factor in the increase of chronic diseases. This condition should be included as a priority in the design of strategies for the intervention in public health; furthermore, the promotion of healthy lifestyles among people becomes a big challenge to health professionals who should face it with creativity and optimism.